How to Determinant Economic Growth In Java Island - Yolanda, Yolanda; Suharto, Suharto; Murti, Wahyu; Haryono, Sugeng (Technium Social Sciences Journal, 2023)
This study aims to provide an emperical picture of the relationship between Investment, Local Original Income, Income Inequality, Unemployment and Crime against Economic Growth of provinces in Java Island using panel data from 2006 to 2021. By using the panel data regression model method, namely the one-way model. Based on the results of data analysis, variables that have a positive and significant effect on economic growth are Investment, Regional Original Income, Income Inequality. And the effect of Unemployment and crime on Economic Growth is significant and negative. Meanwhile, the form of relationship that occurs from all variables to economic growth is inelastic which is shown by the value of a small regression coefficient of one. For this problem it is recommended that local governments make policies that are for investment, local original income, income inequality, unemployment and crime that encourage greater economic growth.